THE CONCEPT OF THE DEVARĀJA IN LEADERSHIP AT THE ROYAL PALACE OF YOGYAKARTA - Assilmi, Ghilman (International Review of Humanities Studies, 2024)
The Yogyakarta Palace is one of the Islamic sultanates that still exists in Indonesia. Even though the Yogyakarta Palace has an Islamic style and has been influenced by modernization which has penetrated aspects of state and society, the embodiment of the God-King concept from ancient Hindu eras remains embedded in the power of the king, state life, and the obedience of the surrounding community to the palace system. This paper has a problem regarding how to apply the concept of politics and power in the Yogyakarta Palace. A historical approach is used to reveal the meaning of the palace in the concept of kingly power and government as well as the cosmic role of the king in the state administration system at the Yogyakarta Palace. The research results show that the sultan as a government leader is also a spiritual leader, which is then depicted in a capital city that is a magical center that signifies harmony between the creator, government/spiritual leaders, and society.